Antimicrobial activities and mechanism of sturgeon spermary protein extracts against Escherichia coli - Chen, Ya-Nan; Li, Hai-Lan; Huang, Jia-Jun; Li, Mei-Jin; Liao, Tao; Zu, Xiao-Yan (Frontiers in Nutrition, 2022)
This study aimed to evaluate the antimicrobial activities and mechanism of sturgeon spermary protein extracts (SSPE) against Escherichia coli. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined. Cell structural change was analyzed using scanning electron microscopy-energy dispersive X-ray spectrometry and transmission electron microscope. Moreover, pH, zeta potential, membrane potential, intracellular ATP concentrations and the interaction of SSPE with genomic DNA were analyzed. Results showed that molecular weight of SSPE is 13.4 kDa, the content of basic amino acids is the highest, in which arginine accounts for 73.2%. The MIC and MBC of SSPE for E. coli were 0.05 and 5 mg/mL, respectively. After SSPE treatment, cell membrane permeability changes, zeta potential decrease and genomic DNA lysis occurred in E. coli, which indicated it exerted bacteriostatic effects either independently or simultaneously by destroying the cell membrane and genomic DNA. These findings indicated that SSPE has potential to be a natural antiseptic.